Developing of Students’ Speaking Proficiency Through Self-Regulated Learning Strategies At Smk Darul Ulum Depok West Java - Ainan Salsabila; Mutiarani Mutiarani (Ridwan Institute, 2022)
In foreign language and teaching in Indonesia, when teaching speaking, most of teachers employ the same strategy. The teacher must change the strategy to be applied to students in order to successfully in the learning process. By using Self-Regulated Learning Strategies can be used to make students improve their learning outcomes. Self-Regulated learning strategies were defined as the strategies used by speakers to control their level of fluency. This research purpose to develop of students’ speaking by using self-regulated learning strategies. The data of this research used Quantitative research method in pre-experimental design. The data sample techniques only used 10 grader BDP A of SMK Darul Ulum Depok, West Java. And the data analyzed used statistically by t-test. The results of this study presented that the mean of students’ pre-test 57.42 and post-test 75.45. The statistic calculation showed that the result of t-calculation (tcal) > t-table (ttable) was 19.040 for t-calculation (tcal) and 2.037 for t-table (ttable) at the significance level of 5% (0.05), indicating that tcal was greater than ttable. Hence, that the Null Hypothesis (H0) was rejected and the Alternative Hypothesis (H1) was accepted. Based on the result, it can be decided that using self-regulated learning strategies can develop to students speaking proficiency.